2004
DOI: 10.1080/00071660400006214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mushroom and herb polysaccharides, as alternatives for an antibiotic, on growth performance of broilers

Abstract: (1) This in vivo trial was conducted to study the effects of polysaccharide extracts of two mushrooms, Lentinus edodes (LenE) and Tremella fuciformis (TreE), and a herb, Astragalus membranaceus (AstE) on growth performance, and the weights of organs and the gastrointestinal tract (GIT) of broiler chickens. (2) Three extracts (LenE, TreE and AstE) were supplemented at inclusion rates of 0.5, 1, 2, 3 and 4 g/kg from 7 to 14 d of age and compared with an antibiotic treatment group (20 mg/kg, virginiamycin (VRG) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 17 publications
3
53
0
2
Order By: Relevance
“…The components of the herbal plants which are responsible for the immune stimulation are not well known. Guo (2003) suggested that the mechanism of medicinal plants components may include improving the physical conditions of gut ecosystem and enhancing function of immune system of chicks. The antioxidant nature of medicinal plants also has been suggested to alleviate the negative influence of environmental stressors and improve immune function to combat different types of diseases (Al-Kassie et al, 2011).…”
Section: Blood Lipids Profilementioning
confidence: 99%
“…The components of the herbal plants which are responsible for the immune stimulation are not well known. Guo (2003) suggested that the mechanism of medicinal plants components may include improving the physical conditions of gut ecosystem and enhancing function of immune system of chicks. The antioxidant nature of medicinal plants also has been suggested to alleviate the negative influence of environmental stressors and improve immune function to combat different types of diseases (Al-Kassie et al, 2011).…”
Section: Blood Lipids Profilementioning
confidence: 99%
“…Several plants and its derivates are extensively studied and used in poultry production including Aloe vera, Astragalus membranaceus, Ginger, Garlic, Noni, Onion, Turmeric and Thyme (Dhama et al, 2015b). These compounds have improved growth of broilers and also increased egg production of layers (Guo et al, 2004;Sunder et al, 2013;Sunder et al, 2014).…”
Section: Antimicrobials Of Plant Origin / Phytobioticsmentioning
confidence: 99%
“…Different levels of EP extract decreased ileal Coliforms population of quails, but ileal Clostridia population of birds consumed EP extract was not different from control group. Guo et al (2004aGuo et al ( , 2004bGuo et al ( , 2004c found that plants derivatives promoted the growth performance, decreased the populations of coliforms and C. perfringens, and boosted both cellular and humoral immune responses of chickens infected with avian Mycoplasma gallisepticum or Eimeria tenella. Jamroz and Kamel (2002) reported that the dietary plant derivatives diminished Escherichia coli population comparing to the control birds.…”
Section: Resultsmentioning
confidence: 99%